Preliminary study of virulence and isozymic variation in natural populations of Colletotrichum gloeosporioides from Stylosanthes guianensis - Lenné, Jillian M.; Burdon, J.J. (Scientific Societies, 1990)
Variation for nine virulence and four electrophoretic characters was determined for 69 samples of Colletotrichum gloeosporioides collected in five natural stands of its host, Stylosanthes guianensis, in South America. Virulence phenotypes varied from four in the Quilichao population to 22 in the Darien population. Isozymic diversity, on the other hand, was limited to a few phenotypes. In contrast to some studies of other fungal pathogens, tight associations between isozyme phenotypes and virulence groupings were not evident. However, the limited number of isozyme phenotypes present and the linkage disequilibrium detected between alleles at several enzyme loci indicate a high level of inbreeding or clonal reproduction in these populations of C. gloeosporioides.